Social and business enterprises : an introduction to organisational economics - Boswell, Jonathan (London : Allen and Unwin, 1976)
This book shows how micro-economics can be used to clarify and stimulate thinking about organisations and their decision making. Unlike many texts in this field, its scope is wide, covering business enterprises, local authorities and a variety of public and voluntary organisations. In highlighting the central theme - the fruitful interaction between abiding economic ideas and contemporary organizational problems - it draws heavily on brief case studies based on actual experience. The principal users are expected to be second and third year undergraduates in polytechnics and universities who are preparing for degrees in economics, other social sciences, management and business studies or public/social administration. The book should also be a suitable introductory text for postgraduate students at business schools and in social administration and for students of these various subjects at technical colleges or colleges of further education.
Includes bibliographical references and index.
rpm 14/11/2017
Loans
Keywords: Microeconomics; Managerial economics; Organization